Respuesta :
Answer:
x = -5 y = -5
Step-by-step explanation:
–x + 4y = -15
- 4y -4y
-1(-x = -4y - 15)
x = 4y + 15
Substitute x = 4y + 15 into 3x + 5y = -40
3(4y + 15) = -40
17y + 45 = -40
- 45 -45
17y = -85
/ 17 /17
y= -5
Substitute y = - 5 into x = 4y + 15:
x = 4(-5) + 15
x = -20 + 15
x = -5
Answer:
Part I
(-5,-5)
Part II
(3.75, 312.50)
Step-by-step explanation:
Part I
(1) 3x + 5y = -40
(2) -x + 4y = -15
solve for x in (2)
x = 15 + 4y
substitute into (1)
3(15+4y) + 5y = -40
45 +12y + 5y = -40
45 +17y = -40
17y = -85
y = -5
substitute y = -5 into (1)
3x + 5(-5) = -40
3x -25 = -40
3x = -15
x = -5
so (-5, -5)
Part II
Studio A
C = 125 + 50t
Studio B
C = 200 + 30t
125 + 50t = 200 + 30t
20t = 75
t = 3.75
(3.75, 312.50)